Comparison of the attitudes of adolescents according to sex and school level towards physical education - Márquez -Barquero, Magally; Azofeifa-Mora, Christian; Rodríguez- Méndez, Diego (Innovaciones Educativas, 2019)
The purpose of the research was to identify the main attitudes that adolescents show towards Physical Education (PE) and compare the behavior according to sex and school level. The Attitudes to Physical Education Questionnaire (C.A.E.F. by its initials in Spanish) a total of 192 participants from 5 educational centers of the third cycle of general basic education. A descriptive analysis of averages and standard deviations, 2x3 ANOVA analysis (2 sexes and 3 levels of schooling), for independent groups and the Tukey post hoc test were carried out. The level of significance established was p < .05. The statistically significant differences were found in the factor Empathy with the teacher and the subject in the variable moderator sex (p = .026) which denotes that men are more empathic than women; while in the variable moderator level of schooling (p = .001), the statistically significant difference was presented in the seventh level, showing that as the level of schooling increases, the empathy towards the teacher and the PE decreases. The Preference factor for Physical Education and Sport (p = .024), the results showed that men outnumber women. As observed, men have a positive attitude towards PE, which suggests that there is greater empathy in men with respect to women and this behavior could be reflected in other areas of physical exercise and sport. Likewise, it decreases the interest in the student body as the age or level of schooling increases.